Ratio-Dependence in Predator-Prey Systems as an Edge and Basic Minimal Model of Predator Interference - Tyutyunov, Yuri V.; Titova, Lyudmila I. (Frontiers in Ecology and Evolution, 2021)
The functional response (trophic function or individual ration) quantifies the average amount of prey consumed per unit of time by a single predator. Since the seminal Lotka-Volterra model, it is a key element of the predation theory. Holling has enhanced the theory by classifying prey-dependent functional responses into three types that long remained a generally accepted basis of modelling predator-prey interactions. However contradictions between the observed dynamics of natural ecosystems and the properties of predator-prey models with Holling-type trophic functions — the paradox of enrichment, the paradox of biological control, and the paradoxical enrichment response mediated by trophic cascades — required further improvement of the theory. This led to idea of inclusion of predator interference into the trophic function. Various functional responses depending on both prey and predator densities have been suggested and compared in their performance to fit observed data. At the end of the 1980s, Arditi and Ginzburg stimulated a lively debate having a strong impact on predation theory. They proposed the concept of a spectrum of predator-dependent trophic functions, with two opposite edges being the prey-dependent and the ratio-dependent cases, and they suggested revising the theory by using the ratio-dependent edge of the spectrum as a null model of predator interference. Ratio-dependence offers the simplest way of accounting for mutual interference in predator-prey models, resolving the above-mentioned contradictions between theory and natural observations. Depending on practical needs and availability of observations, the more detailed models can be built on this theoretical basis.